The ankle in XLH: Reduced motion, power and quality of life - Akta, Celine; Wenzel-Schwarz, Florian; Stauffer, Alexandra; Kranzl, Andreas; Raimann, Adalbert; Kocijan, Roland; Ganger, Rudolf; Mindler, Gabriel T. (Frontiers in Endocrinology, 2023)
Background X-linked hypophosphatemia (OMIM 307800) is a rare bone disease caused by a phosphate-wasting condition with lifelong clinical consequences. Those affected suffer from bone pain, complex skeletal deformities, impaired mobility and a reduced quality of life. Early osteoarthritis and reduced range of motion of the lower limbs are known pathologies in XLH patients. However, XLH-specific data on the affected compartments such as the ankle joint through the evaluation of radiographic and gait analysis data is still lacking. Patients and Methods In this cross-sectional study, patients with genetically verified XLH, age ≥ 16 - 50 years and a complete record of gait analysis and or radiographic analysis data were included. Clinical examination, radiological and gait analysis data were compared to norms using the dataset of our gait laboratory registry. Radiographic analysis included tibial deformity analysis and assessment of osteoarthritis and enthesopathies. Western Ontario and McMaster Universities Arthritis Index (WOMAC), SF36v2, American Orthopedic Foot and Ankle Society score (AOFAS) and the Foot and Ankle Outcome Score (FAOS) were used. Twentythree participants with 46 limbs were eligible for the study. Results A total of 23 patients (n=46 feet) met the inclusion criteria. Patients with XLH had significantly reduced gait quality, ankle power and plantar flexion (p < 0.001) compared to a historic gait laboratory control group. Ankle valgus deformity was detected in 35 % and ankle varus deformity in 17.5 % of the patients. The subtalar joint (59.1 %) as well as the anterior tibiotalar joint (31.1 %) were the main localizations of moderate to severe joint space narrowing. Ankle power was decreased in moderate and severe subtalar joint space narrowing (p < 0.05) compared to normal subtalar joint space narrowing. No lateral or medial ligament instability of the ankle joint was found in clinical examination. Tibial procurvatum deformity led to lower ankle power (p < 0.05). Conclusions This study showed structural and functional changes of the ankle in patients with XLH. Subtalar ankle osteoarthritis, patient reported outcome scores and clinical ankle restriction resulted in lower gait quality and ankle power.